2015
DOI: 10.1186/s13028-015-0161-8
|View full text |Cite
|
Sign up to set email alerts
|

A retrospective cohort study on fertility in the Norwegian Coldblooded trotter after artificial insemination with cooled, shipped versus fresh extended semen

Abstract: BackgroundPregnancy rates with cooled equine semen can be unsatisfactory and show great variation. Information about first cycle pregnancy rates and pregnancy rates per cycle are often lacking from publicly available records. This retrospective cohort study was performed to evaluate the fertility of the Norwegian Coldblooded trotter. The aim of the study was to compare the breeding results after insemination with fresh, extended with those of cooled, shipped semen among Norwegian Coldblooded trotter mares. Fir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 12 publications
1
7
2
Order By: Relevance
“…10 A study on the fertility of Norwegian Coldblood trotters under AI conditions reported an FCPR of 51.2%. 22 A study incorporating 11 farms in Victoria, Australia reported a FCPR of 65.3%-75% in Thoroughbreds (7 farms) and 57.1%-74.0% in Standardbreds (4 farms). 1 Our current study showed considerably greater variability in FCPR for mares inseminated both on-farm (range 52.7%-72.5%) and off-farm (range 49.7%-67.3%) and we contend that this may reflect the differences in mare age and semen type.…”
Section: Discussionmentioning
confidence: 99%
“…10 A study on the fertility of Norwegian Coldblood trotters under AI conditions reported an FCPR of 51.2%. 22 A study incorporating 11 farms in Victoria, Australia reported a FCPR of 65.3%-75% in Thoroughbreds (7 farms) and 57.1%-74.0% in Standardbreds (4 farms). 1 Our current study showed considerably greater variability in FCPR for mares inseminated both on-farm (range 52.7%-72.5%) and off-farm (range 49.7%-67.3%) and we contend that this may reflect the differences in mare age and semen type.…”
Section: Discussionmentioning
confidence: 99%
“…Also in the present study, the FH mares were about one year older than the SB mares. The negative effect of ageing on mare fertility has been reported in all studies where mare age has been included as a factor [1,[21][22][23][24][25][26][27]. Age affects many aspects of reproduction, such as uterine function (uterine contractility, intrauterine fluid accumulation, endometrial inflammation and fibrosis), PR and pregnancy loss [22].…”
Section: Mare Agementioning
confidence: 98%
“…These selection methods, although undeniably producing champions, have consequently led to a decline in fertility [ 1 , 2 ]. While limited information is available for the per cycle conception rates in standardbred horses alone, other breeds, which also utilize artificial insemination (AI), have indicated pregnancy rates per cycle range from 76% to 83% [ 3 , 4 , 5 ] after AI using fresh semen and pregnancy rates of 44–69% after AI using chilled semen [ 5 , 6 , 7 , 8 ]. Several factors have been observed to impact reproductive efficiency, including the age of the stallion and mare, the mare’s reproductive history (e.g., maiden, barren, foal heat), the month of breeding, genotype, frequency of mating, and endocrine levels [ 9 , 10 , 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%